2014
DOI: 10.1186/1471-2458-14-1137
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to particle health effects, miRNA and exosomes: rationale and study protocol of the SPHERE study

Abstract: BackgroundDespite epidemiological findings showing increased air pollution related cardiovascular diseases (CVD), the knowledge of the involved molecular mechanisms remains moderate or weak. Particulate matter (PM) produces a local strong inflammatory reaction in the pulmonary environment but there is no final evidence that PM physically enters and deposits in blood vessels. Extracellular vesicles (EVs) and their miRNA cargo might be the ideal candidate to mediate the effects of PM, since they could be potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 59 publications
1
56
0
Order By: Relevance
“…(Bollati, 2014a, Bollati et al, 2014b) The study subjects were predominantly female (80% of the population), 122 were obese (66%) and 64 were overweight (34%), with a mean age of 51 years.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bollati, 2014a, Bollati et al, 2014b) The study subjects were predominantly female (80% of the population), 122 were obese (66%) and 64 were overweight (34%), with a mean age of 51 years.…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies have shown that obesity may confer greater susceptibility to the adverse effects of PM exposure, since adipocytes have increased particle accumulation (Bollati et al, 2014b; Dubowsky et al, 2006) A positive correlation between exhaled nitric oxide, a marker of pulmonary inflammation, and BMI has been shown in healthy adults (De Winter-de Groot et al, 2005) Moreover, a differential autonomic cardiac response (measured as heart rate variability) to metal particles has been observed between obese and non-obese individuals (Chen et al, 2007). Obesity represents a pro-inflammatory state (Jacobsen et al, 2016, Karkeni et al, 2016) which itself may increase susceptibility to air pollution by increasing the response to inflammatory stimuli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obese individuals were chosen for this study due to their increased susceptibility to the effects of air pollution (due to a higher particle accumulation rate) (Bennett and Zeman, 2004, Bollati et al, 2014). We identified and validated a distinct signature of nine miRNAs (miR-145, miR-197, miR-30b, miR-345, miR-26a, miR-425–5p, miR-331, miR-140–3p, and miR-101) in the peripheral blood, which were associated with PM 10 exposure levels 48 h after exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Ninety overweight and obese subjects were recruited at the Center for Obesity and Work (Fondazione IRCCS Cà Granda Ospedale Maggiore Policlinico in Milan, Lombardia, Italy) from September 2010 to January 2011 as part of the cross-sectional SPHERE study (Bollati et al, 2014). Each participant provided written informed consent before inclusion in the study, which was approved by the Ethics Committee of Fondazione IRCCS Cà Granda Ospedale Maggiore Policlinico (approval number 1425).…”
Section: Methodsmentioning
confidence: 99%